Dont' touch! - Kline, Suzy (Morton Grove, Illinois : Albert Whitman & Company, 1985)
When all the grown-ups constantly say, "Don't touch!" Dan finds somehting he can safely squeeze, smash, and pound to his heart's content.
Keywords: Children's stories, America; Behavior-fiction